0358 Defining Existing Practices to Support the Sleep of Hospitalized Patients: A Mixed-Methods Study of Top-Ranked Hospitals. (25th May 2022) - Affini, Murtala; Arora, Vineet; Gulati, Jasmine; Mason, Noah; Klein, Aviva; Clarke, Karen; Cho, Hyung; Lee, Vivian; McDaniel, Lauren; Orlov, Nicola
Abstract: Introduction: While sleep is critical for health, the hospital is not conducive to patient sleep and few efforts have been made to improve. The current practices to promote hospitalized inpatient sleep at highly-ranked hospitals are unknown. Methods: A mixed-methods study of Hospital Medicine Section Chiefs at the 2020 US News and World Report Honor Roll pediatric and adult hospitals was conducted to understand the current practices and attitudes towards inpatient sleep between June and August 2021. An anonymous, quantitative survey was disseminated to quantify current practices and satisfaction with sleep-friendly institutional efforts. Survey participants were invited to share their institutions' progress and potential ways to further improve inpatient sleep during structured, qualitative interviews. Results: Pediatric (n=10) and adult (n=20) section chiefs were queried. Survey response rate was 77% (n=23/30; pediatric n=8/10; adult n=15/20). While 96% (n=22) of hospitalist leaders rated sleep as important, only 43% (n=10) were satisfied with their institution's efforts to improve patient sleep. Although 91% (n=21) of hospitalist leaders rated sleep equity as important, one institution (4%) had practices in place to address the issue. Less than half (n=11) of institutions reported having sleep-friendly practices. Among these institutions, the most common practices included: reducing overnight vital sign monitoring (91%, n=10), decreasing ambient light in the wards (91%, n=10), adjusting lab and medication schedules (73%, n=8), and implementing quiet hours (64%, n=7). Twenty-seven percent of hospitalist leaders (n=8/30; pediatric interviews=3/10; adult interviews=5/20) participated in interviews. Themes included: the importance of having a sleep-friendly culture, environmental changes, modified hospital practices, and external incentives to improve patient sleep. Conclusion: Hospitalists recognize the importance of improving patient sleep, but few institutions have sleep-friendly practices in place. Most institutions have no sleep health equity practices in place in their hospital. Building sleep-friendly hospital cultures and establishing best practices should be a priority for clinicians. Support (If Any): The authors thank the Society of Hospital Medicine and the Pritzker School of Medicine for funding support.